Opportunities. Intermediate Student's Book with Mini-Dictionary - Harris M. Michael (Harlow, Longman, 2002)
Modules of topic-based units provide rich, contemporary content based о wide variety of informative themes. With a discovery approach to grammar and an upfront focus on vocabulary, ensures +he most effective language learning for teenagers.